Incomplete company law reform : the treasury shares question in South Africa - Gondwe, Ruth Dinah (Department of Commercial Law, 2015)
One of the paradoxes in company law is the phenomenon of treasury shares. Their complex nature coupled with the risks attached to their use has rendered them problematic and unnecessary in modern company law. Refuting arguments stated against the use of treasury shares, this paper aims to build a case for the introduction of treasury shares into South African company law. In order to achieve this, the paper will firstly examine the nature and complexity of treasury shares. Thereafter, it will discuss their importance in modern company law by highlighting their commercial value. A study of their incorporation into a few jurisdictions will also be discussed in an attempt to propose a manner in which South Africa can introduce treasury shares into its law. It is a suggestion of this contribution that the recent company law reform was a missed opportunity to adopt treasury shares. The adoption of treasury shares would have been an indication of a complete breakup from traditional straitjacket concept of capital maintenance. However, as they were not adopted when the new Companies Act 71 of 2008 this paper will propose, in conclusion, that treasury shares ought to be adopted.